Fall Prevention: How To Handle a Fall - Leigh Ann Martin (EDIS)
Follow the steps in this document to decrease the chance of further injury after a fall. This document is FCS2233, one in a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL 32611. Publication date: April 2005.